Application of Mann-Whitney U-test in the analysis of gender-based leadership and collaborative scholarly writing performance - Wonu, Nduka; Anaekwe, Eugenia (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2023)
The study investigated the gender-based variations in scholarly writing performance in a collaborative book with a focus on leadership. The study adopted a comparative research design, guided by four research objectives and corresponding hypotheses. The collaborative book writing involved contributions from 73 authors across 30 chapters, of which 16 were led by male authors, and 14 were led by female authors. The 30 chapters were subjected to Grammarly Software to determine the performance of the authors in a collaborative scholarly writing task. The study meticulously analyzed variables such as overall writing performance (text quality), word count metrics (characters, words, sentences), readability patterns (word length, sentence length, overall readability score), and vocabulary richness (unique words, rare words). Descriptive statistics such as mean, standard deviation, ranking and graphs were used to answer the research questions whereas the Mann-Whitney U-test was used to test the hypotheses at a .05 level of significance. The findings established among others that the gender of the lead author had no significant influence on the overall writing performance and vocabulary richness. However, subtle variations were identified in readability patterns, specifically in sentence length. These methodologically robust findings challenge preconceptions about gender-specific writing tendencies and provide a foundation for targeted recommendations to enhance equity in collaborative scholarly writing.